The effectiveness of hydrocolloid dressings versus other dressings in the healing of pressure ulcers in adults and older adults: a systematic review and meta-analysis - Franciele Soares Pott; Marineli Joaquim Meier; Janislei Giseli Dorociak Stocco; Karla Crozeta; Janyne Dayane Ribas (Universidade de São Paulo, 2014)
OBJECTIVE: to evaluate the effectiveness of hydrocolloids in the healing of pressure ulcers in adult and older adult patients.METHOD: systematic review with meta-analysis, based on the recommendations of the Cochrane Handbook. The search was undertaken in the databases: Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Health Sciences Literature (LILACS), Cochrane Database, Cumulative Index to Nursing and Allied Health Literature, Web of Science and the Scientific Electronic Library Online.RESULTS: 646 primary studies were identified, 69 were evaluated and nine were selected, referring to the use of the hydrocolloid dressing in healing; of these, four studies allowed meta-analysis. There was no statistically significant difference between the hydrocolloid group and the foams group (p value=0.84; Odds Ratio 1.06, CI 95% 0.61-1.86). A slight superiority of the polyurethane dressings was observed in relation to the hydrocolloid dressings.CONCLUSION: the evidence is not sufficient to affirm whether the efficacy of hydrocolloid dressings is superior to that of other dressings. It is suggested that clinical randomized trials be undertaken so as to ascertain the efficacy of this intervention in the healing of pressure ulcers, in relation to other treatments.